Single switch Z-source/quasi Z-source DC-DC converters - V Saravanan; M Sabitha; V Bindu; Venkatachalam K M; M. Arumugam (International Journal of Applied Power Engineering (IJAPE), 2021)
This paper analyzes a family of high step up single switch switched capacitor boost converters and Z-source/quasi Z-source dc-dc converters to provide high output dc voltage gain with single stage conversion having low voltage stress on active switches, capacitors, and diodes. The operating principles, parameters design guideline of these converters are presented along with simulation results. The discussed topologies in this paper are aimed to increase the conversion system reliability and efficiency with decreased cost, volume, and weight. These power converter topologies are used for various applications such as photovoltaic (PV) systems, wind energy conversion, fuel cells, uninterruptible power systems, motor drives, energy storage systems, electric vehicle and power factor correction. Simulations are carried out in MATLAB/Simulink environment.